Scrotal neoplasia: would truck drivers be at greater risk? - Daniel Seabra; Gilberto Fava; Eliney Faria; Teoclito Sacheto; Geraldo Hidalgo (International Brazilian Journal of Urology, 2007)
OBJECTIVE: To analyze how scrotal neoplasias have been managed during the past decade and to question possible factors or professions associated to its presence. MATERIALS AND METHODS: We retrospectively evaluated every case reported from 1995 to 2005 at our hospital. We described the clinical scenario, complementary exams, treatments and outcomes. We also tried to verify if there was any risk, predisposing factors or professions that would explain the cancer origin. RESULTS: Six cases were reviewed. Out of these, three patients were truck drivers. Five of them showed restricted lesions without inguinal lymph nodes enlargement. Histologically, six patients presented squamous carcinoma, with two of them having the verrucous type. The median age of patients was 52 years old (31 to 89). The five patients who are still alive had their lesions completely removed with safety margin and primary closure. CONCLUSIONS: We have noticed that the scrotal carcinoma behavior is similar to that of the penis, where removal of the lesion and study of the regional lymph nodes help to increase the patient survival rate. The outstanding fact was that three out of six patients were truck drivers, raising the hypothesis that such profession, maybe due to the contact or attrition with the diesel exhaust expelled by the engine or to sexual promiscuity, would imply in a larger risk of developing this rare neoplasia.